Positive electrode active material for non-aqueous electrolyte secondary battery, non-aqueous electrolyte secondary battery, and method for producing positive electrode active material for non-aqueous electrolyte secondary battery

By using a high NI -content lithium transition metal composite oxide in the positive active substance of the lithium -ion battery, and fixed the SO4 compounds on its surface to form a protective layer, solve the problem of insufficient loading and discharge loading characteristics of lithium -ion batteries, and realize it. A better cycle characteristics and initial capacity.

CN115023830BActive Publication Date: 2025-01-28PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202080093954.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-01-31
Filing Date
2020-12-03
Publication Date
2025-01-28
Estimated Expiration
2040-12-03

AI Technical Summary

Technical Problem

In the prior art, there is still room for improvement in the charge and discharge cycle characteristics of nonaqueous electrolyte secondary batteries such as lithium-ion batteries, especially when the Ni content is high, the problem of initial capacity is easily reduced.

Method used

The lithium transition metal composite oxides containing more than 80 Moor % or more are used as positive active substances, and the compound containing SO4 is fixed on its surface to form a protective layer by heat treatment to improve the cycle characteristics of the battery.

Benefits of technology

Through this method, it can significantly improve the charging and discharge cycle characteristics of non -hydrolytic secondary batteries, reduce the generation of cationic mixed, improve the initial capacity, and inhibit the decomposition response of the electrolyte.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115023830B_ABST
    Figure CN115023830B_ABST
Patent Text Reader

Abstract

A positive electrode active material for a non-aqueous electrolyte secondary battery, which is a positive electrode active material comprising a lithium transition metal composite oxide, wherein the lithium transition metal composite oxide contains 80 mol% or more of Ni relative to the total molar number of metal elements other than Li, contains at least one of Mn and Al, and contains at least one metal element selected from Co, W, Mg, Mo, Nb, Ti, Si, Zr, Fe, Zn, Er, K, Pr, Ca, Ba, Sc, Rb, Ga, In, Sn and Sr, the total amount of Mn and Al relative to the total molar number of metal elements other than Li is 5 mol% or more, and for a filtrate of a suspension prepared by adding 250 mg of the positive electrode active material to 10 mL of a 17.5 mass % hydrochloric acid aqueous solution, heating and dissolving at 90° C. for 2 hours, and diluting to 50 mL, the amount of S dissolved in the filtrate determined by inductively coupled plasma mass spectrometry is 0.002 mmol or more.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a positive electrode active material for a nonaqueous electrolyte secondary battery, a nonaqueous electrolyte secondary battery using the positive electrode active material, and a method for producing the positive electrode active material. Background Art

[0002] Lithium transition metal composite oxides are usually used as positive electrode active materials for non-aqueous electrolyte secondary batteries such as lithium ion batteries. In recent years, lithium transition metal composite oxides with a high Ni content have been widely used as high-capacity positive electrode active materials. For example, Patent Document 1 discloses a method for manufacturing a positive electrode active material in which tungsten oxide is fixed to the surface of particles of lithium transition metal composite oxide containing Ni, and at least one selected from sulfuric acid compounds, nitric acid compounds, boric acid compounds and phosphoric acid compounds is fixed to the composite particles, and the composite particles are heat-treated in an oxygen atmosphere.

[0003] Prior art literature

[0004] Patent Literature

[0005] Patent Document 1: Japanese Patent Application Publication No. 2010-040383 Summary of the invention

[0006] For non-aqueous electrolyte secondary batteries such as lithium ion batteries, improving the charge and discharge cycle characteristics is an important issue. In the prior art including the technology disclosed in Patent Document 1, there is still room for improvement in the cycle characteristics of the battery. It should be noted that when the manufacturing method disclosed in Patent Document 1 is used, when the Ni content ratio in the positive electrode active material is high, cation mixing occurs and the initial capacity is easily reduced.

[0007] A positive electrode active material for a nonaqueous electrolyte secondary battery according to one embodiment of the present disclosure is a positive electrode active material comprising a lithium transition metal composite oxide, wherein the lithium transition metal composite oxide contains 80 mol% or more of Ni relative to the total molar number of metal elements other than Li, contains at least one of Mn and Al, and contains at least one metal element selected from Co, W, Mg, Mo, Nb, Ti, Si, Zr, Fe, Zn, Er, K, Pr, Ca, Ba, Sc, Rb, Ga, In, Sn and Sr, wherein the total amount of Mn and Al is 5 mol% or more relative to the total molar number of metal elements other than Li, and for a filtrate of a suspension prepared by adding 250 mg of the positive electrode active material to 10 mL of a 17.5 mass % aqueous hydrochloric acid solution, heating and dissolving the mixture at 90° C. for 2 hours, and diluting the suspension to 50 mL, the amount of S eluted in the filtrate determined by inductively coupled plasma mass spectrometry is 0.002 mmol or more.

[0008] A nonaqueous electrolyte secondary battery according to one embodiment of the present disclosure includes a positive electrode including the positive electrode active material for a nonaqueous electrolyte secondary battery, a negative electrode, and a nonaqueous electrolyte.

[0009] A method for manufacturing a positive electrode active material for a non-aqueous electrolyte secondary battery as one embodiment of the present invention includes: a step of oxidizing and roasting a hydroxide containing at least Ni obtained by a crystallization method to obtain a composite oxide; a step of mixing the composite oxide and a lithium compound and calcining the mixed particles to obtain a lithium transition metal composite oxide; and a step of washing the lithium transition metal composite oxide with water, mixing the composite oxide with at least one selected from cobalt sulfate, magnesium sulfate, titanium sulfate, zirconium sulfate, iron sulfate, zinc sulfate, erbium sulfate, potassium sulfate, praseodymium sulfate, calcium sulfate, barium sulfate, scandium sulfate, rubidium sulfate, gallium sulfate, indium sulfate, tin sulfate and strontium sulfate, and heat treating the mixture under vacuum conditions at a temperature of 150 to 280°C.

[0010] According to the positive electrode active material disclosed in the present invention, a non-aqueous electrolyte secondary battery with excellent charge-discharge cycle characteristics can be provided. That is, for a non-aqueous electrolyte secondary battery containing a positive electrode active material containing 80 mol % or more of Ni relative to the total molar number of metal elements other than Li, the charge-discharge cycle characteristics can be improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0011] Figure 1 It is a cross-sectional view of a nonaqueous electrolyte secondary battery as an example of an embodiment. DETAILED DESCRIPTION

[0012] As mentioned above, for non-aqueous electrolyte secondary batteries such as lithium ion batteries, improving the charge and discharge cycle characteristics is an important issue. The inventors of the present invention have focused on the positive electrode active material and conducted in-depth research to improve the cycle characteristics. As a result, it was found that when the filtrate of the suspension formed by the positive electrode active material being dispersed in a specified hydrochloric acid aqueous solution contains a specified amount of S, the cycle characteristics of the battery are specifically improved. It can be seen that this effect is manifested when the total content of Mn and Al in the positive electrode active material is more than 5 mol%. The detailed mechanism of the improvement of the cycle characteristics is unclear, but it is believed that S as a dissolved component originates from SO4, and the compound containing SO4 functions as a protective layer on the particle surface of the lithium transition metal composite oxide, inhibiting the decomposition reaction of the electrolyte on the particle surface, thereby improving the cycle characteristics. It is assumed that when a specified amount of S is present in the filtrate, the function of the protective layer is fully manifested.

[0013] The following is a detailed description of an example of an embodiment of a positive electrode active material for a non-aqueous electrolyte secondary battery disclosed in the present invention, a non-aqueous electrolyte secondary battery using the positive electrode active material, and a method for manufacturing the positive electrode active material, with reference to the accompanying drawings. The following example shows a cylindrical battery in which a wound electrode body 14 is accommodated in a cylindrical battery case, but the electrode body is not limited to a wound type, and may also be a stacked type in which a plurality of positive electrodes and a plurality of negative electrodes are alternately stacked by a separator. In addition, the non-aqueous electrolyte secondary battery disclosed in the present invention may also be a square battery having a square metal case, a coin-shaped battery having a coin-shaped metal case, etc., or a laminated battery having an outer body composed of a laminate sheet comprising a metal layer and a resin layer.

[0014] Figure 1 FIG. 1 is a cross-sectional view of a nonaqueous electrolyte secondary battery 10 as an example of an embodiment. Figure 1 As shown in the example, the nonaqueous electrolyte secondary battery 10 includes an electrode body 14, an electrolyte, and a battery case 15 that accommodates the electrode body 14 and the nonaqueous electrolyte. The electrode body 14 includes a positive electrode 11, a negative electrode 12, and a separator 13, and has a winding structure in which the positive electrode 11 and the negative electrode 12 are wound through the separator 13. The battery case 15 is composed of an outer can 16 in a cylindrical shape with a bottom and a sealing body 17 that blocks the opening of the outer can 16.

[0015] The non-aqueous electrolyte contains a non-aqueous solvent and an electrolyte salt dissolved in the non-aqueous solvent. The non-aqueous solvent may be, for example, esters, ethers, nitriles, amides, and mixed solvents of two or more thereof. The non-aqueous solvent may contain a halogen substituted substance in which at least a portion of the hydrogen of these solvents is replaced with a halogen atom such as fluorine. It should be noted that the non-aqueous electrolyte is not limited to a liquid electrolyte and may be a solid electrolyte. The electrolyte salt may be, for example, a lithium salt such as LiPF6.

[0016] The nonaqueous electrolyte secondary battery 10 includes insulating plates 18 and 19 disposed above and below the electrode body 14 , respectively. Figure 1 In the example shown, the positive electrode lead 20 attached to the positive electrode 11 extends to the sealing body 17 side through the through hole of the insulating plate 18, and the negative electrode lead 21 attached to the negative electrode 12 extends to the bottom side of the outer can 16 through the outside of the insulating plate 19. The positive electrode lead 20 is connected to the lower surface of the bottom plate 23 of the sealing body 17 by welding or the like, and the top plate of the sealing body 17, that is, the lid 27 electrically connected to the bottom plate 23 forms a positive terminal. The negative electrode lead 21 is connected to the bottom inner surface of the outer can 16 by welding or the like, and the outer can 16 forms a negative terminal.

[0017] The outer can 16 is, for example, a metal container in a cylindrical shape with a bottom. A gasket 28 is provided between the outer can 16 and the sealing body 17 to ensure the airtightness of the battery interior. The outer can 16 is formed with a groove 22 that supports the sealing body 17, for example, a portion of the side portion protruding inward. The groove 22 is preferably formed in an annular shape along the circumferential direction of the outer can 16, and supports the sealing body 17 on its upper surface.

[0018] The sealing body 17 has a structure in which a bottom plate 23, a lower valve core 24, an insulating member 25, an upper valve core 26, and a cover 27 are stacked in order from the electrode body 14 side. The components constituting the sealing body 17 have, for example, a disc shape or a ring shape, and the components except the insulating member 25 are electrically connected to each other. The lower valve core 24 and the upper valve core 26 are connected to each other at their respective central portions, and the insulating member 25 is sandwiched between their respective peripheral portions. If the internal pressure of the battery increases due to abnormal heat generation, the lower valve core 24 is deformed and broken in a manner that pushes the upper valve core 26 to the cover 27 side, and the current path between the lower valve core 24 and the upper valve core 26 is blocked. Furthermore, if the internal pressure increases, the upper valve core 26 breaks, and gas is discharged from the opening of the cover 27.

[0019] The positive electrode 11 , the negative electrode 12 , and the separator 13 constituting the electrode body 14 , and in particular the positive electrode active material contained in the positive electrode 11 , will be described in detail below.

[0020] [positive electrode]

[0021] The positive electrode 11 includes a positive electrode collector and a positive electrode composite material layer formed on at least one side of the collector. The positive electrode collector can use a foil of a metal such as aluminum or aluminum alloy that is stable in the potential range of the positive electrode 11, a thin film of the metal configured on the surface, etc. The positive electrode composite material layer preferably includes a positive electrode active material, a conductive material, and a binding material, and is formed on both sides of the positive electrode collector. The positive electrode 11 can be manufactured as follows: a positive electrode composite material slurry containing a positive electrode active material, a conductive material, and a binding material is applied to the positive electrode collector, and after the coating is dried, the coating is compressed to form the positive electrode composite material layer on both sides of the positive electrode collector, thereby manufacturing the positive electrode 11.

[0022] As the conductive material contained in the positive electrode composite material layer, carbon materials such as carbon black, acetylene black, Ketjen black, and graphite can be illustrated. As the binding material contained in the positive electrode composite material layer, fluororesins such as polytetrafluoroethylene (PTFE) and polyvinylidene fluoride (PVdF), polyacrylonitrile (PAN), polyimide, acrylic resin, polyolefin, etc. can be illustrated. These resins, cellulose derivatives such as carboxymethyl cellulose (CMC) or its salt, polyethylene oxide (PEO), etc. can be used in combination.

[0023] The positive electrode active material contains more than 80 mol% Ni relative to the total molar number of metal elements other than Li, and contains at least one of Mn and Al, and contains at least one metal element selected from Co, W, Mg, Mo, Nb, Ti, Si, Zr, Fe, Zn, Er, K, Pr, Ca, Ba, Sc, Rb, Ga, In, Sn and Sr. Here, the total amount of Mn and Al is more than 5 mol% relative to the total molar number of metal elements other than Li. The positive electrode active material uses the composite oxide as the main component, and the content of the composite oxide in the positive electrode active material is preferably more than 90 mass %, and can actually be 100 mass %. It should be noted that the positive electrode active material may contain lithium transition metal composite oxides or other compounds other than the composite oxide within the range that will not damage the effect of the present disclosure. Unless otherwise specified below, the lithium transition metal composite oxide refers to the above-mentioned composite oxide with a Ni content of more than 80 mol%.

[0024] The lithium transition metal composite oxide may contain 85 mol% or more of Ni, or 90 mol% or more of Ni, relative to the total molar number of metal elements other than Li. The Ni content is, for example, 80 to 95 mol%. An example of a suitable lithium transition metal composite oxide is a general formula Li a Ni (1-x-y) M1 x M2 y A composite oxide represented by O2 (0.97≤a≤1.2, 0.05≤x≤0.2, 0≤y≤0.1, 0.05≤x+y≤0.2, M1 is at least one of Al and Mn, and M2 is at least one metal element selected from Co, W, Mg, Mo, Nb, Ti, Si, Zr, Fe, Zn, Er, K, Pr, Ca, Ba, Sc, Rb, Ga, In, Sn and Sr). It should be noted that the above-mentioned lithium transition metal composite oxide may contain elements other than Li, Ni, metal element M1 and metal element M2 such as Na, V, In, Y, Cr within the range that does not impair the effect of the present disclosure.

[0025] The above-mentioned lithium transition metal composite oxide is usually a secondary particle formed by the aggregation of primary particles. The volume-based median particle size of the lithium transition metal composite oxide (secondary particle) is not particularly limited, and is preferably 2μm to 20μm, and more preferably 6μm to 15μm. The volume-based median particle size of the composite oxide is the particle size with a volume cumulative value of 50% in the particle size distribution measured using a laser diffraction scattering particle size distribution measuring device, also known as the 50% particle size (D50). The particle size of the primary particles constituting the secondary particles is, for example, 0.05μm to 2μm. The particle size of the primary particles is measured as the diameter of the circumscribed circle in the particle image observed using a scanning electron microscope (SEM).

[0026] For the positive electrode active material containing the above-mentioned lithium transition metal composite oxide, 250 mg of the positive electrode active material is added to 10 mL of a 17.5 mass % hydrochloric acid aqueous solution, heated and dissolved at 90°C for 2 hours, and the filtrate is diluted to 50 mL of the suspension. The amount of S dissolved in the filtrate obtained by inductively coupled plasma mass spectrometry (ICP-MS) is 0.002 mmol% or more. When the amount of S dissolved does not meet this condition, as shown in the examples described later, good cycle characteristics cannot be obtained. The presence of sulfate ions (SO4 2- ), Li ions may not be present.

[0027] The specific quantitative method of the eluted components of the positive electrode active material is as follows.

[0028] (1) 250 mg of the positive electrode active material is added to 10 mL of a 17.5 mass % hydrochloric acid aqueous solution and heated at 90° C. for 2 hours to dissolve the active material, thereby preparing a suspension in which the active material is dispersed in the aqueous solution. The temperature during the preparation of the suspension may be about 90° C., for example, 90° C.±5° C.

[0029] (2) The suspension is filtered (solid-liquid separation) to obtain a filtrate containing dissolved components such as S. The filtrate is then diluted to 50 mL with distilled water.

[0030] (3) The eluted components in the filtrate are quantified using an ICP-MS device.

[0031] The S in the filtrate is a dissolved component derived from a compound containing SO4 (hereinafter sometimes referred to as a "compound containing SO4"), and it is believed that the positive electrode active material contains a compound containing SO4. The compound containing SO4 is present, for example, on the surface of particles of the lithium transition metal composite oxide. The compound containing SO4 may be present inside the secondary particles, that is, on the surface of the primary particles that are not shown on the surface of the secondary particles (the interface between the primary particles), but it is preferably present more on the surface of the secondary particles than inside the secondary particles.

[0032] The SO4-containing compound is preferably present on the entire surface of the lithium transition metal composite oxide particles at a uniform density on average. It is assumed that the SO4-containing compound present on the surface of the lithium transition metal composite oxide particles functions as a protective layer to inhibit the decomposition reaction of the electrolyte on the particle surface. It is believed that when the filtrate contains S at a concentration of 0.002 mmol or more, the function of the protective layer realized by the SO4-containing compound is fully manifested and the cycle characteristics of the battery are improved.

[0033] The amount of S dissolved in the filtrate is preferably 0.003 mmol or more. The upper limit of the amount of S dissolved is not particularly limited from the viewpoint of cycle characteristics, but is preferably 0.24 mmol in consideration of battery capacity, output power, etc. The amount of S dissolved is, for example, 0.003 to 0.03 mmol.

[0034] The elution amount of the metal element M (at least one metal element selected from Co, W, Mg, Ti, Zr, Fe, Zn, Er, K, Pr, Ca, Ba, Sc, Rb, Ga, In, Sn and Sr) contained in the filtrate is preferably 0.0001 mmol or more. The upper limit of the elution amount of the metal element M is not particularly limited from the viewpoint of cycle characteristics, but is preferably 0.3 mmol in consideration of battery capacity, output power, etc.

[0035] It should be noted that the compound containing SO4 present on the particle surface of the lithium transition metal composite oxide is conceivably selected from at least one of lithium sulfate, cobalt sulfate, magnesium sulfate, titanium sulfate, zirconium sulfate, iron sulfate, zinc sulfate, erbium sulfate, potassium sulfate, praseodymium sulfate, calcium sulfate, barium sulfate, scandium sulfate, rubidium sulfate, gallium sulfate, indium sulfate, tin sulfate and strontium sulfate. For example, at least lithium sulfate is present on the particle surface of the lithium transition metal composite oxide. In addition, hydroxides or oxides of Co, Mg, Ti, Zr, Fe, Zn, Er, K, Pr, Ca, Ba, Sc, Rb, Ga, In, Sn, Sr, etc. may be present on the particle surface of the lithium transition metal composite oxide.

[0036] The Li contained in the positive electrode active material is preferably 7.4% by mass or less, more preferably 7.3% by mass or less, and particularly preferably 7.1% by mass or less. The amount of Li can be 7.0% by mass or less, but at this time the charging capacity is likely to decrease and the reaction resistance is likely to increase. If the amount of Li exceeds 7.4% by mass, the positive electrode composite material slurry used in the formation of the positive electrode composite material layer is gelled, and it is difficult to form a high-quality positive electrode composite material layer. The positive electrode active material is manufactured by adding a prescribed sulfuric acid compound to the washed lithium transition metal composite oxide and heat-treating it at low temperature and in a vacuum state, which can suppress the generation of cation mixing and reduce the amount of Li dissolved.

[0037] In addition to the compound containing SO4, at least one of tungsten oxide (WO3) and lithium tungstate generated by the reaction of the excess Li of the lithium transition metal composite oxide with WO3 can also be fixed on the particle surface of the lithium transition metal composite oxide. WO3 and lithium tungstate are preferably fixed to the entire particle surface of the lithium transition metal composite oxide at a uniform density, similarly to the compound containing SO4. In the case where WO3 and lithium tungstate exist on the particle surface, the cycle characteristics of the battery are further improved by the synergistic effect with the compound containing SO4. The content of WO3 and lithium tungstate is preferably 0.05 to 0.5 mol% relative to the total molar number of metal elements other than Li of the lithium transition metal composite oxide in terms of W element conversion. In order to minimize the reduction in charging capacity, it is particularly preferably 0.05 to 0.2 mol%.

[0038] WO3 and lithium tungstate are fixed on the surface of the particles of lithium transition metal composite oxide, and their content can be observed and quantified using SEM and ICP emission spectrometer. It should be noted that phosphorus compounds, boron compounds, rare earth compounds and other SO4-containing compounds and inorganic particles other than WO3 and lithium tungstate can exist on the surface of the particles of lithium transition metal composite oxide.

[0039] The positive electrode active material containing the above-mentioned lithium transition metal composite oxide is preferably added to a mixed solution of 100 mL of pure water, 1 mL of a 35% by mass hydrochloric acid aqueous solution, 0.05 mL of a 46% by mass hydrofluoric acid, and 0.05 mL of a 64% by mass nitric acid. 1 g of the positive electrode active material is stirred for 5 minutes, and the mixed solution is filtered to obtain a filtrate. For the filtrate, the ratio of the partial dissolution amount of the metal element M contained in the filtrate obtained by ICP-MS to the total dissolution amount of the metal element M obtained in the same manner when 1g of the positive electrode active material is completely dissolved ((partial dissolution amount / total dissolution amount) × 100) is 50% or more, more preferably 55% or more. The partial dissolution amount measured by this method indicates the amount of metal element M present on the surface and near the positive electrode active material (the same applies to S). When the dissolution amount ratio of the metal element M meets this condition, it exhibits excellent cycle characteristics compared to the case where it is not satisfied.

[0040] The total dissolution amount of the positive electrode active material was calculated as follows: 200 mg of the positive electrode active material was added to a mixed solution of 5 mL of 35 mass % hydrochloric acid, 2.5 mL of 46 mass % hydrofluoric acid, and 2.5 mL of 64 mass % nitric acid, and the mixed solution was heated at about 90°C for 2 hours. Pure water was added to the mixed solution and the volume was fixed to 100 mL, and the total dissolution amount of the positive electrode active material was calculated by ICP-MS.

[0041] The positive electrode active material can be produced by a production method including the following steps.

[0042] (1) A step of oxidatively calcining a hydroxide containing at least Ni obtained by a crystallization method to obtain a composite oxide.

[0043] (2) A step of mixing a composite oxide and a lithium compound and firing the mixed particles to obtain a lithium transition metal composite oxide.

[0044] (3) After washing the lithium transition metal composite oxide with water, the composite oxide is mixed with at least one selected from cobalt sulfate, magnesium sulfate, titanium sulfate, zirconium sulfate, iron sulfate, zinc sulfate, erbium sulfate, potassium sulfate, praseodymium sulfate, calcium sulfate, barium sulfate, scandium sulfate, rubidium sulfate, gallium sulfate, indium sulfate, tin sulfate and strontium sulfate, and the mixture is heat-treated at a temperature of 150 to 280° C. under vacuum conditions.

[0045] In step (1), for example, a hydroxide containing Ni, Co, and Al can be obtained by a coprecipitation method using nickel sulfate, cobalt sulfate, and aluminum sulfate as raw materials. The hydroxide is calcined (oxidative roasting) at 500 to 700° C. in the atmosphere for 1 to 3 hours to obtain a composite oxide containing Ni, Co, and Al. The composite oxide obtained in step (1) contains at least Ni and at least one of Al and Mn, and preferably also contains Co. In addition, the composite oxide obtained in step (1) may contain Mo, Nb, and Si.

[0046] In step (2), the mixture of the composite oxide and the lithium compound obtained in step (1) is calcined at a temperature exceeding 700°C. The preferred range of the calcination temperature is 700 to 900°C. The calcination is preferably carried out in an oxygen flow. In step (2), a lithium compound is usually used in excess of the stoichiometric ratio of the target product. Examples of lithium compounds include lithium carbonate, lithium hydroxide, lithium nitrate, and lithium sulfate. Among them, lithium carbonate and lithium hydroxide are preferred. In addition, it is preferred to crush and classify the lithium transition metal composite oxide before proceeding to step (3) to adjust D50 to within a specified range.

[0047] In step (3), the lithium transition metal composite oxide obtained in step (2) is washed with water and solid-liquid separation is performed to obtain a powder of the composite oxide having a moisture content of 3 to 8% by mass. At least one selected from cobalt sulfate, magnesium sulfate, titanium sulfate, zirconium sulfate, iron sulfate, zinc sulfate, erbium sulfate, potassium sulfate, praseodymium sulfate, calcium sulfate, barium sulfate, scandium sulfate, rubidium sulfate, gallium sulfate, indium sulfate, tin sulfate and strontium sulfate is added to the powder of the composite oxide and mixed. Here, these sulfuric acid compounds may be hydrates. In addition, the addition amount of these sulfuric acid compounds is preferably 0.01 to 0.5 mol% relative to the total molar number of metal elements other than Li of the lithium transition metal composite oxide in terms of metal element conversion of Co, Mg, Ti, Zr, Fe, Zn, Er, K, Pr, Ca, Ba, Sc, Rb, Ga, In, Sn or Sr. At this time, tungsten oxide may be added together with the above-mentioned sulfuric acid compounds.

[0048] The mixed powder of the lithium transition metal composite oxide and the sulfuric acid compound is heat treated under vacuum at a low temperature of 150 to 280°C. The heat treatment temperature is more preferably 150 to 210°C. By heat treating the mixed powder at a low temperature and in a vacuum state, the generation of cation mixing can be suppressed, and a positive electrode active material having a protective layer of a compound containing SO4 formed on the particle surface of the lithium transition metal composite oxide can be obtained. It should be noted that if the heat treatment of step (3) is carried out under an oxygen atmosphere (in the air), cation mixing will occur and the initial capacity will decrease.

[0049] As the raw materials of the hydroxide of step (1), nickel sulfate, cobalt sulfate and aluminum sulfate are used. When titanium sulfate is added in step (3), the metal elements contained in the positive electrode active material are, for example, Li, Ni, Co, Al, and Ti. At this time, for the filtrate of the suspension of 250 mg of the positive electrode active material added to 10 mL of a 17.5 mass % hydrochloric acid aqueous solution, heated and dissolved at 90° C. for 2 hours, and diluted to 50 mL, the amount of S dissolved in the filtrate obtained by ICP-MS is 0.002 mmol or more. The non-aqueous electrolyte secondary battery using the positive electrode active material exhibits excellent cycle characteristics.

[0050] [negative electrode]

[0051] The negative electrode 12 includes a negative electrode current collector and a negative electrode composite material layer formed on at least one side of the current collector. The negative electrode current collector may be made of a foil of a metal such as copper or a copper alloy that is stable in the potential range of the negative electrode 12, or a film in which the metal is arranged on the surface. The negative electrode composite material layer preferably includes a negative electrode active material and a binding material, and is formed on both sides of the negative electrode current collector. The negative electrode 12 can be manufactured as follows: a negative electrode composite material slurry containing a negative electrode active material, a binding material, etc. is applied to the negative electrode current collector, and after the coating is dried, the coating is rolled to form the negative electrode composite material layer on both sides of the current collector, thereby manufacturing the negative electrode 12.

[0052] As the negative electrode active material, there is no particular limitation as long as it can reversibly absorb and release lithium ions, and carbon materials such as graphite are generally used. Graphite can be any of natural graphites such as flaky graphite, blocky graphite, and earthy graphite, blocky artificial graphite, and artificial graphites such as graphitized mesophase carbon microbeads. In addition, as the negative electrode active material, metals such as Si and Sn alloyed with Li, metal compounds containing Si, Sn, etc., lithium-titanium composite oxides, etc. can be used. Examples of compounds containing Si include SiO x Si-containing compounds represented by (0.5≤x≤1.5), etc.

[0053] The binder contained in the negative electrode composite material layer can use fluororesins such as PTFE and PVdF, PAN, polyimide, acrylic resin, polyolefin, etc., similarly to the case of the positive electrode 11, preferably styrene-butadiene rubber (SBR). In addition, the negative electrode composite material layer can contain CMC or its salt, polyacrylic acid (PAA) or its salt, PVA, etc. The negative electrode composite material layer contains, for example, SBR and CMC or its salt.

[0054] [Separator]

[0055] The separator 13 uses a porous sheet having ion permeability and insulation. Specific examples of the porous sheet include microporous films, woven fabrics, nonwoven fabrics, etc. The material of the separator 13 is preferably polyolefins such as polyethylene and polypropylene, cellulose, etc. The separator 13 can be a single-layer structure or a laminated structure. In addition, a resin layer with high heat resistance such as aramid resin or a filler layer containing a filler of an inorganic compound can be provided on the surface of the separator 13.

[0056] <Example>

[0057] The present disclosure will be described in more detail below through examples, but the present disclosure is not limited to these examples.

[0058] <Example 1>

[0059] [Preparation of positive electrode active material]

[0060] The nickel-cobalt-aluminum composite hydroxide obtained by the coprecipitation method was oxidized and roasted to synthesize Ni 0.85 Co 0.10 Al 0.05 The composite oxide is shown in Figure 2. The composite oxide and lithium hydroxide are mixed in a manner such that the molar ratio of the metal element in the composite oxide to Li in the lithium hydroxide is 1:1.015, and the mixture is calcined at 745°C for 6 hours under an oxygen flow, and the calcined product is crushed and classified to obtain a lithium transition metal composite oxide having a D50 of 12 μm. The lithium transition metal composite oxide is a secondary particle formed by the aggregation of primary particles.

[0061] 1250 g of lithium transition metal composite oxide was put into 1 L of water for washing and solid-liquid separation to obtain a powder of composite oxide with a water content of 3 to 8% by mass. The composite oxide powder was mixed with titanium sulfate, and the mixed powder was heat-treated at 180° C. under vacuum conditions for 3 hours to obtain a positive electrode active material. Here, the amount of titanium sulfate added was calculated in terms of Ti element conversion, and the total molar number of metal elements other than Li in the lithium transition metal composite oxide was 0.1 mol%.

[0062] The amounts of S and metal element M (Ti) eluted from the positive electrode active material were quantified according to the following procedure. The measurement results are shown in Table 1 (the same applies to the following Examples and Comparative Examples).

[0063] (1) 250 mg of the positive electrode active material was added to 10 mL of a 17.5 mass % hydrochloric acid aqueous solution and heated to dissolve at 90° C. for 2 hours to prepare a suspension in which the active material was dispersed in the aqueous solution.

[0064] (2) The suspension was filtered and diluted to 50 mL with distilled water to obtain a filtrate containing S and M.

[0065] (3) Using an ICP-MS apparatus (SPS3100 manufactured by Hitachi High-Tech Science Corporation), S and M in the filtrate were quantified.

[0066] [Evaluation of the ratio of the elution amount of metal elements M and S]

[0067] By the above method, the partial elution amount and total elution amount of the metal elements M and S in the obtained positive electrode active material were determined, and their ratios ((partial elution amount / total elution amount)×100) were calculated. The measurement results are shown in Table 1 (the same applies to the following Examples and Comparative Examples).

[0068] [Production of positive electrode]

[0069] The positive electrode active material, acetylene black and polyvinylidene fluoride (PVdF) were mixed at a solid content mass ratio of 100:0.75:0.6 to prepare a positive electrode composite material slurry using N-methyl-2-pyrrolidone (NMP) as a dispersion medium. Next, the positive electrode composite material slurry was applied to both sides of a positive electrode collector formed of aluminum foil, the coating was dried and compressed, and then cut into a specified electrode size to prepare a positive electrode having a positive electrode composite material layer formed on both sides of the positive electrode collector.

[0070] [Production of negative electrode]

[0071] As the negative electrode active material, graphite and SiO x A mixture of Si-containing compounds represented by (x=1.0) in a mass ratio of 96:4. The negative electrode active material, a dispersion of styrene butadiene rubber (SBR), and sodium carboxymethyl cellulose (CMC-Na) are mixed in a solid content mass ratio of 98:1:1 to produce a negative electrode composite material slurry using water as a dispersion medium. Next, the negative electrode composite material slurry is applied to both sides of a negative electrode collector formed of copper foil, and after the coating is dried and compressed, it is cut into a specified electrode size to produce a negative electrode having a negative electrode composite material layer formed on both sides of the negative electrode collector.

[0072] [Manufacturing of non-aqueous electrolyte]

[0073] Ethylene carbonate (EC), methyl ethyl carbonate (MEC), and dimethyl carbonate (DMC) were mixed at a volume ratio of 20:5:75. LiPF6 was dissolved in the mixed solvent to a concentration of 1.2 mol / L, thereby preparing a non-aqueous electrolyte.

[0074] [Battery production]

[0075] An aluminum lead was installed on the positive electrode, a nickel lead was installed on the negative electrode, and the positive electrode and the negative electrode were wound into a spiral shape by a polyethylene separator, thereby manufacturing a wound electrode body. The electrode body was accommodated in a bottomed cylindrical battery case body with an outer diameter of 18.2 mm and a height of 65 mm, and after the non-aqueous electrolyte was injected, the opening of the battery case body was sealed by a gasket and a sealing body, thereby manufacturing a cylindrical non-aqueous electrolyte secondary battery.

[0076] <Comparative Example 1>

[0077] A positive electrode active material and a battery were obtained by the same method as in Example 1 except that titanium sulfate was not added in the preparation of the positive electrode active material.

[0078] [Evaluation of Cycle Characteristics (Capacity Retention Rate)]

[0079] Each battery of Example 1 and Comparative Example 1 was charged at 25°C with a constant current of 0.3It until the battery voltage was 4.2V, and then charged at a constant voltage of 4.2V until the current was 70mA, which was the termination current. Then, it was discharged at a constant current of 0.5It until the battery voltage was 2.5V. This charge and discharge cycle was repeated 100 times, and the ratio of the discharge capacity of the 100th cycle to the discharge capacity of the 1st cycle (capacity retention rate) was calculated. The capacity retention rate of the battery of Comparative Example 1 was set to a relative value of 100, and the capacity retention rate of the battery of Example 1 is shown in Table 1.

[0080] [Table 1]

[0081]

[0082] <Example 2>

[0083] In the preparation of the positive electrode active material, Ni 0.85 Co 0.05 Al 0.10 A positive electrode active material and a battery were obtained by the same method as in Example 1 except that the composite oxide represented by O2 was used.

[0084] <Comparative Example 2>

[0085] In the preparation of the positive electrode active material, Ni 0.85 Co 0.05 Al 0.10 A positive electrode active material and a battery were obtained by the same method as in Comparative Example 1 except for the composite oxide represented by O2.

[0086] The cycle characteristics were evaluated using the batteries obtained in Example 2 and Comparative Example 2. The capacity retention rate of the battery of Example 2 is shown in Table 2, with the capacity retention rate of the battery of Comparative Example 2 being a relative value of 100.

[0087] [Table 2]

[0088]

[0089] <Example 3>

[0090] In the preparation of the positive electrode active material, Ni 0.91 Co 0.035 Al 0.055 A positive electrode active material and a battery were obtained by the same method as in Example 1 except that the composite oxide represented by O2 was used.

[0091] <Comparative Example 3>

[0092] In the preparation of the positive electrode active material, Ni 0.91 Co 0.035Al 0.055 A positive electrode active material and a battery were obtained by the same method as in Comparative Example 1 except for the composite oxide represented by O2.

[0093] The cycle characteristics were evaluated using the batteries obtained in Example 3 and Comparative Example 3. The capacity retention rate of the battery of Comparative Example 3 was set as a relative value of 100, and the capacity retention rate of the battery of Example 3 is shown in Table 3. Furthermore, the capacity retention rate at a high voltage was measured in the same manner as in the evaluation of the above cycle characteristics, except that the voltage during charging was increased from 4.2 V to 4.3 V, and the capacity retention rate of the battery of Comparative Example 3 was set as a relative value of 100, and the results for Example 3 are shown.

[0094] [Table 3]

[0095]

[0096] <Example 4>

[0097] In the preparation of the positive electrode active material, Ni 0.92 Al 0.055 Mn 0.025 A positive electrode active material and a battery were obtained by the same method as in Example 1 except that the composite oxide represented by O2 was used.

[0098] <Comparative Example 4>

[0099] In the preparation of the positive electrode active material, Ni 0.92 Al 0.055 Mn 0.025 A positive electrode active material and a battery were obtained by the same method as in Comparative Example 1 except for the composite oxide represented by O2.

[0100] The cycle characteristics were evaluated using the batteries obtained in Example 4 and Comparative Example 4. The capacity retention rate of the battery of Example 4 is shown in Table 4, with the capacity retention rate of the battery of Comparative Example 4 being a relative value of 100.

[0101] [Table 4]

[0102]

[0103] <Comparative Example 5>

[0104] In the preparation of the positive electrode active material, Ni 0.82 Co 0.15 Al 0.03 A positive electrode active material and a battery were obtained by the same method as in Example 1 except that the composite oxide represented by O2 was used.

[0105] <Comparative Example 6>

[0106] In the preparation of the positive electrode active material, Ni 0.82 Co 0.15 Al 0.03 A positive electrode active material and a battery were obtained by the same method as in Comparative Example 1 except for the composite oxide represented by O2.

[0107] The cycle characteristics were evaluated using the batteries obtained in Comparative Examples 5 and 6. The capacity retention rate of the battery of Comparative Example 6 was set as a relative value of 100, and the capacity retention rate of the battery of Comparative Example 5 is shown in Table 5.

[0108] [Table 5]

[0109]

[0110] As shown in Tables 1 to 4, the batteries of the embodiments have higher capacity retention rates after the cycle test and better cycle characteristics than the batteries of the corresponding comparative examples. For the batteries of Comparative Examples 1 to 4, the S contained in the filtrate is less than 0.002 mmol, and the ratio of the elution amount of the metal elements M and S is less than 50%. When the S contained in the filtrate is 0.002 mmol or more, and the ratio of the elution amount of the metal elements M and S is 50% or more, a high-quality positive electrode composite material layer can be formed, and the cycle characteristics of the battery are specifically improved.

[0111] Description of Reference Numerals

[0112] 10 Non-aqueous electrolyte secondary battery

[0113] 11 Positive electrode

[0114] 12 Negative electrode

[0115] 13 Divider

[0116] 14 Electrode body

[0117] 15 Battery housing

[0118] 16 Outer can

[0119] 17 Sealing body

[0120] 18, 19 Insulation board

[0121] 20 Positive lead

[0122] 21 Negative lead

[0123] 22 Groove

[0124] 23 Base Plate

[0125] 24 Lower valve core

[0126] 25 Insulation components

[0127] 26 Upper valve core

[0128] 27 Cover

[0129] 28 Pad

Claims

1. A positive electrode active material for a non-aqueous electrolyte secondary battery, which is a positive electrode active material comprising a lithium transition metal composite oxide, wherein the lithium transition metal composite oxide contains 80 mol % or more of Ni relative to the total molar number of metal elements other than Li, contains at least one of Mn and Al, and contains at least one metal element selected from Co, W, Mg, Mo, Nb, Ti, Si, Zr, Fe, Zn, Er, K, Pr, Ca, Ba, Sc, Rb, Ga, In, Sn and Sr, The total amount of Mn and Al is 5 mol% or more relative to the total molar number of metal elements excluding Li, Titanium sulfate exists on the particle surface of the lithium transition metal composite oxide. The amount of S dissolved in the filtrate obtained by inductively coupled plasma mass spectrometry was 0.002 mmol or more in a filtrate obtained by adding 250 mg of the positive electrode active material to 10 mL of a 17.5 mass % hydrochloric acid aqueous solution, heating and dissolving the mixture at 90° C. for 2 hours, and diluting the mixture to 50 mL of the suspension. The method for producing the positive electrode active material comprises the following steps: A step of oxidizing and roasting a hydroxide containing at least Ni obtained by a crystallization method to obtain a composite oxide; A step of mixing the composite oxide and a lithium compound and firing the mixed particles to obtain a lithium transition metal composite oxide; and A process of washing the lithium transition metal composite oxide with water, mixing the composite oxide with titanium sulfate, and heat-treating the mixture at a temperature of 150 to 280° C. under vacuum conditions.

2. The positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 1, wherein For the lithium transition metal composite oxide, the dissolution amount of the metal element M contained in the filtrate is greater than 0.0001 mmol, wherein the metal element M is at least one metal element selected from Co, W, Mg, Ti, Zr, Fe, Zn, Er, K, Pr, Ca, Ba, Sc, Rb, Ga, In, Sn and Sr.

3. The positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 1 or 2, wherein 1 g of the lithium transition metal composite oxide is added to a mixed solution of 100 mL of pure water, 1 mL of a 35% by mass hydrochloric acid aqueous solution, 0.05 mL of a 46% by mass hydrofluoric acid, and 0.05 mL of a 64% by mass nitric acid, and after stirring for 5 minutes, the mixed solution is filtered to obtain a filtrate, wherein the ratio of the partial elution amount of S and the metal element M in the filtrate obtained by inductively coupled plasma mass spectrometry to the total elution amount of S and the metal element M obtained in the same manner when 1 g of the lithium transition metal composite oxide is completely dissolved ((partial elution amount / total elution amount)×100) is 50% or more, The metal element M is at least one metal element selected from Co, W, Mg, Ti, Zr, Fe, Zn, Er, K, Pr, Ca, Ba, Sc, Rb, Ga, In, Sn and Sr.

4. The positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 1 or 2, wherein At least one of tungsten oxide and lithium tungstate is fixed to the surface of the lithium transition metal composite oxide particles.

5. The positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 3, wherein At least one of tungsten oxide and lithium tungstate is fixed to the surface of the lithium transition metal composite oxide particles. 6 . A non-aqueous electrolyte secondary battery comprising: a positive electrode comprising the positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 1 , a negative electrode, and a non-aqueous electrolyte.

7. A method for producing a positive electrode active material for a non-aqueous electrolyte secondary battery, which is the method for producing a positive electrode active material for a non-aqueous electrolyte secondary battery according to any one of claims 1 to 5, comprising: A step of oxidizing and roasting a hydroxide containing at least Ni obtained by a crystallization method to obtain a composite oxide; A step of mixing the composite oxide and a lithium compound and firing the mixed particles to obtain a lithium transition metal composite oxide; and A process of washing the lithium transition metal composite oxide with water, mixing the composite oxide with titanium sulfate, and heat-treating the mixture at a temperature of 150 to 280° C. under vacuum conditions.

Citation Information

Patent Citations

  • Method of manufacturing positive electrode active material, and positive electrode active material

    JP2010040383A

  • Positive electrode active material for nonaqueous electrolyte secondary batteries and nonaqueous electrolyte secondary battery using said positive electrode active material

    CN108352524A

  • Positive electrode for non-aqueous electrolytic secondary cells, positive electrode active substance, method for manufacturing positive electrode active substance and non-aqueous electrolytic secondary cells

    CN109478644A

  • Positive electrode active substance material, positive electrode for nonaqueous electrolyte secondary battery, and nonaqueous electrolyte secondary battery

    JP2019121607A